Arguments on Social Media: A Conceptual Analysis of Senior High School Students’ Election-Related Facebook Posts - Cabreros, Dhemer P. (Future Science / FSH-PH Publications, 2024)
This study analyzed the arguments, specifically the fallacies and the posting strategies present on the eleven (11) Facebook posts of the WCC Aeronautical and Technological College senior high school students on election-related issues. The researcher utilized conceptual analysis using deductive method in this study. The fallacies and posting strategies were tallied and ranked, categorized based on the emerging themes, and subjected to conceptual analysis. The 11 fallacies were categorized into three themes based on the rhetorical triangle and the themes that emerged are influence in facts, influence in credibility, and influence in emotions. On the other hand, four themes emerged in the posting strategies: praising, sarcasm, name-calling and invalidating, and straightforwardness, where positive impoliteness garnered the highest number of commissions. There are also other themes that emerged in the analysis of data: the image functions and the communication styles.